Electrostatically-blind quantitative piezoresponse force microscopy free of distributed-force artifacts. Issue 8 (29th March 2022) - Killgore, Jason P.; Robins, Larry; Collins, Liam
Abstract : Electrostatic forces complicate the interpretation of piezoresponse force microscopy (PFM). Electrostatic blind spot (ESBS) PFM overcomes these complications by placing the detection laser where it is sensitive piezoresponse but not electrostatics. Abstract : The presence of electrostatic forces and associated artifacts complicates the interpretation of piezoresponse force microscopy (PFM) and electrochemical strain microscopy (ESM). Eliminating these artifacts provides an opportunity for precisely mapping domain wall structures and dynamics, accurately quantifying local piezoelectric coupling coefficients, and reliably investigating hysteretic processes at the single nanometer scale to determine properties and mechanisms which underly important applications including computing, batteries and biology. Here we exploit the existence of an electrostatic blind spot (ESBS) along the length of the cantilever, due to the distributed nature of the electrostatic force, which can be universally used to separate unwanted long range electrostatic contributions from short range electromechanical responses of interest. The results of ESBS-PFM are compared to state-of-the-art interferometric displacement sensing PFM, showing excellent agreement above their respective noise floors. Ultimately, ESBS-PFM allows for absolute quantification of piezoelectric coupling coefficients independent of probe, lab or experimental conditions. As such, we expect the widespread adoption of EBSB-PFM to be a paradigm shift in the quantification of nanoscale electromechanics.